Voices of Islam in Southeast Asia : a contemporary sourcebook - Fealy, Greg, 1957-; Hooker, Virginia Matheson, 1946-; Institute of Southeast Asian Studies (Singapore : Institute of Southeast Asian Studies, 2006)
Designed to promote an understanding of Muslim attitudes to major political, legal, religious and social issues in Southeast Asia, this book includes quotations from documents on Islamic law; state and governance; jihad; society, women and the family; and more. It is useful for government officials, academics, security analysts, and journalists.
PART I: INTRODUCTION; 1. Voices of Islam in Southeast Asia: A Contemporary Sourcebook by Greg Fealy and Virginia Hooker; PART II: COUNTRY OVERVIEWS AND CONTEXT OF SOUTHEAST ASIAN ISLAM; 2. Brunei Darussalam by John Funston; 3. Burma by Curt Lambrecht; 4. Cambodia and Vietnam by Jacob Ramsay; 5. Indonesia by Greg Fealy, Virginia Hooker and Sally White; 6. Malaysia by John Funston; 7. Philippines by Kit Collier; 8. Singapore by John Funston; 9. Thailand by John Funston; PART III: EXTRACTS FROM PRIMARY SOURCES; 10. Personal Expressions; 11. Shari'ah (Islamic Law); 12. Islam, State and Governance; 13. Gender and the Family; 14. Jihad; 15. Interactions: Global and Local; Muslims and Non-Muslims.
References : p. 481-492
Sumbangan Mohamad Taha (2017).
Keywords: Islam -- Asia, Southeastern; Islam -- Doctrines; Islam -- Customs and practices; Islam and state -- Southeast Asia; Muslim women -- Southeast Asia; Jihad